Modelling of low temperature oxidation of coal dumps. - Kaitano, Rufaro. (My University, 1998)
Storage and waste dumps from coal mining tend to spontaneously combust. This is mainly as a result of the oxidation process which is accelerated by the availability of oxygen and the exothermic nature of the oxidation process. In cases of poor ventilation the heat accumulation within the bed is thought to lead to the spontaneous combustion of coal. The work in this dissertation aims to investigate the change in oxygen concentration in a bed of coal and also measure the rate of oxidation (oxygen absorption) in a closed reactor under isothermal conditions. Drying rate of coal under nitrogen was also looked into. An analysis of the oxygen concentration profile in a three metre 20 cm ID plastic column filled up with coal has been carried out. As the coal ages (becomes oxidised) its reactivity towards oxygen decreases and changes in the oxygen concentration profile are noticed. Experiments have been carried out up to 8 months and from the results obtained, a simple pseudo-steady-state model has been developed to describe the diffusion of oxygen into a reacting coal bed. The findings could prove useful in trying to find a solution to coal and waste dump fire control. The second experiment is a simple isothermal oxygen absorption experiment in which the rate of absorption of oxygen on a given coal sample is measured at different initial concentrations of oxygen. The initial concentration of oxygen is varied over a fairly wide range in order to determine the dependence of the rate of oxidation on the oxygen concentration. The rate- limiting step in low temperature oxidation of coal is found to be the absorption of oxygen. Moisture also plays a role in coal oxidation. Drying experiments were also carried out so as to quantify and investigate the rate of loss of moisture. Models have been developed which try to explain tile mechanisms involved in the drying process. The modelling suggest that the bound water model is more appropriate to the type of behaviour exhibited during the drying process.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, for the Degree of Master of Science.
Keywords: Coal mines and mining -- Waste dispossal.; Gold mines and mining.; Coal ash sites.